The Anatomy of Developmental Predictors of Healthy Lives Study (TADPOHLS). Issue 2 (2nd April 2016) - Kern, Margaret L.; Benson, Lizbeth; Larson, Emily; Forrest, Christopher B.; Bevans, Katherine B.; Steinberg, Laurence
Abstract : Numerous studies have followed people across significant portions of their lives. Secondary analyses with these studies offer opportunities to study life trajectories across diverse samples. To aid integrative efforts, we introduce The Anatomy of Developmental Predictors of Healthy Lives Study (TADPOHLS), a data base that categorizes items and constructs from 14 prospective longitudinal studies that followed participants from adolescence into adulthood. To classify items and measures, we created an extensive typology that provides a common language for categorizing study concepts. We illustrate the utility of the data base by examining adolescent perseverance and optimism as predictors of physical health outcomes across six studies. Adolescent perseverance and optimism were related to better physical health outcomes 15 to 20 years later. Overall, the data base offers a resource that contributes toward life-span studies of positive psychological and physical health.